(untitled) (CIPEEX, 2026)
INTRODUCTION: Anxiety and depression are prevalent mental disorders in the world population. However, it is importante to note that certain groups are predisposed to them, and among these groups are university professors, as there are several factors that predisose them to anxiety and depression. OBJECTIVE: To analyze the correlation between the epidemiology of the main mental disorders and the use of psychotropic medication among university professors at the university UniEvangélica of Goiás from january to august 2025. METHODS: The study used a cross-sectional method and appropriate instruments for data collection and analysis, applying online sociodemographic questionnaires, including the Hospital Anxiety and Depression Scale (HADS) for symptom assessment. RESULTS: Men had a slightly higher prevalence of anxiety than women, but the prevalence of depression was higher in women. Depression was more prevalent in women who were married and worked more than 40 hours a week. With regard to the use of medication 49,98% of the participants used psychotropic drugs, especially sertraline, quetiapine and desvenlafaxine. However, only 23% of those interviewed underwent regular therapy. CONCLUSION: The results highlight the need for institutional policies and strategies aimed at teachers’ mental health.